Juicios expresados por niñas y niños de 9 a 11 años de edad sobre comportamientos y actitudes que conducen a la aceptación o al rechazo social en un grupo escolar (2007)
The aim of this study was to identify behaviors and attitudes that children, between the 9 and 11 years of age, associate with the acceptance and the social rejection within a school group. Children were asked to make estimations about the importance that different qualities and defects have as factors that contribute to that a boy could be accepted, or on the contrary, feel the rejection of its schoolmates. To collect the information, tree measuring instruments were used: a socio-metric test, a questionnaire on qualities that contribute a child to enjoy to be accepted and a questionnaire on defects that lead to the rejection of the partnerships. These instruments were applied collectively in the classroom, but it was asked each boy to respond independently without commenting its answers with its classmates. The collected data were process statistically through variance and correlation analysis. Most of the children's answer coincided on the degree of importance of some qualities and some defects. The degree of social integration shown social integration shown by the children within its scholar group did not seem to affect significant form the judgments that expressed. The results suggest some prototypes profiles of accepted and rejected children to the interior of the scholar groups. Keywords: Acceptance, Reject, Qualities, Defects, Pairs, Judgments.